Undetectable HCV‐RNA at treatment‐week 8 results in high‐sustained virological response in HCV G1 treatment‐experienced patients with advanced liver disease: the International Italian/Spanish Boceprevir/Peginterferon/Ribavirin Name Patients Program. Issue 5 (14th October 2014) - Bruno, S.; Bollani, S.; Zignego, A. L.; Pascasio, J. M.; Magni, C.; Ciancio, A.; Caremani, M.; Mangia, A.; Marenco, S.; Piovesan, S.; Chemello, L.; Babudieri, S.; et al.
Summary In many countries, first‐generation protease inhibitors (PIs)/peginterferon/ribavirin (P/R) still represent the only treatment option for HCV‐infected patients. Subjects with advanced disease and previous failure to P/R urgently need therapy, but they are under‐represented in clinical trials. All treatment‐experienced F3/4 Metavir patients who received boceprevir (BOC)+P/R in the Italian–Spanish Name Patient Program have been included in this study. Multivariate logistic regression analysis (MLR) was used to identify baseline and on‐treatment predictors of SVR and adverse events (AEs). Four hundred and sixteen patients, mean age 57.7 (range 25–78 years), 70% males, 69.5% (289/416) F4, 14% (41/289) Child–Pugh class A6, 24% (70/289) with varices and 42% (173/416) prior null responders to P/R, were analysed. Overall, SVR rate (all 381 patients who received one dose of BOC) was 49%, (58% in F3, 45% in F4, 61% in relapsers, 51% in partial, 38% in null responders, and 72% in subjects with undetectable HCV‐RNA at treatment‐week (TW)8. Among patients with TW8 HCV‐RNA ≥ 1000 IU/L, SVR was 8% (negative predictive value = 92%). Death occurred in 3 (0.8%) patients, while decompensation and infections were observed in 2.9% and 11%, respectively. At MLR, SVR predictors were TW4 HCV‐RNA ≥ 1log10‐decline from baseline, undetectable TW8 HCV‐RNA, prior relapse, albumin levels ≥3.5 g/dL and platelet counts ≥100 000/μL. Metavir F4, Child‐Pugh A6, albumin, platelets, age and female gender were associated with serious and haematological AEs. Among treatment‐experienced patients with advanced liver disease eligible for IFN‐based therapy, TW8 HCV‐RNA characterised the subset with either high or poor likelihood of achieving SVR. Using TW8 HCV‐RNA as a futility rule, BOC/P/R appears to have a favourable benefit–risk profile.